Desenvolvimento e caracterização de compósito cimentício leve para elementos de vedação no contexto de smart buildings - Pereira, Antonio de Araujo (2021)
The e fficient and rational use of energy can be promoted constructive improv ments in the envelomysof buildings in accordance with the performance, adding new Technologies and alternative materials, as it acts directly in all consumer systems of the building. Smart buildings are buildings capable of saving energy, as well as contributing to sustainability goals. They should be able tomaximizetheuseof resources through technologies already available, both constructive and use of materials, or even high tech industry technologies. In view of the above, this work aims to develop a light cementitious composite, using expanded clay as aggregate, and elaborate a prototype masonry element aiming at its application in the wrapping of buildings.The materials used for the production of cementitious composites were: CPV ARI cement; expanded clay of 2,50 mm (lamelar) granulometry; expanded clay of granulometry 5,00 mm. For the characterization of the materials, the tests of: unit mass were carried out and volume of voids according to NBR NM 45:2006; specific masses and absorption according to NBR NM 52:2009. The test for granulometric determination of the aggregates was performed according to ABNT NBR 248:2003, and were classified according to NBR 7211:2005. In a second moment experimental compositions (traces) were performed in three proportions 1:4, 1:5, and 1:6 (Cement:Expanded Clay:water). For each trace, with initial content of expanded clay 2,50 mm, 100% by mass, substitutions were performed by expanded clay of 5,00 mm at the levels of 0%, 25% and 50%. Of these compositions, nine mass strokes tested for compressive strength in accordance with NBR 6136-2014 were tested. The mild cementitious composites were characterized at the macro level: simple compression reisitence, porosity, specific mass, absorption and void index, thermal conductivity, coefficient attenuation, as well as microstructural characterization via MEV. Finally, a prototype of sealing element was designed and executed with a view to initiating the practical application of the study. The results obtained, with regard to the mechanical properties (NBR 36:2004) and the physical properties of composites qualify the composites cementis obtained from TR 1(100%), TR 2(75%) and TR 3(50%), as mild cementitious composites. As for thermal performance, composites mild cementitious obtained from TR 1(100%), TR 2(75%) and TR 3(50%) had an average conductivity of 0.13 W/m.K, which corresponds to 7.6% conductivity of conventional concrete. The lightweight precast lightweight lightweight masonry element, from TR 3(50%) trace molding presents good results regarding its behavior regarding the attenuation of electromagnetic waves, when compared with the results found in the bibliography. In general, the technical feasibility of making sealing elements using light cementitious composites with expanded clay and its application in smart buildings can be seen.